Technology - Neale, Margaret A.; Mannix, Elizabeth A., 1960- (Research on managing groups and teams, 2000)
This third volume in the series presents research on technology as either a tool or context for groups and teams. The volume is more broad than some other treatments of technology and groups. Thirteen chapters by leaders from both organizational behavior and information technology present management issues from two critical perspectives: groups and teams in evolving high-tech contexts (e.g., high precision manufacturing, computer virus assessment, space shuttle mission control, minimally invasive cardiac surgery); and leading edge research on technology for communication and knowledge management within groups and teams. The latter including research on virtual teams, adaptive structuration theory, conflict management, and the management of status and deception in electronic mail. Each chapter presents a unique view of groups and teams in modern organizational environments. Readers in the fields of management, organizational behavior, management information systems, information technology, social psychology, technology management and engineering will find useful results and interpretations for both research and practice. The summary chapter by Professor Linda Argote provides an integration and starting point for future assessments of technology, groups, and teams.